Copyright in the music industry : a practical guide to exploiting and enforcing rights - Bosher, Hayleigh (Elgar practical guides, 2021)
"This must-have book is a comprehensive yet accessible guide to copyright and related rights in the music industry. It provides clear and concise instruction on how copyright works in practice and how it applies to music specifically, as well as covering how to manage, utilise and enforce copyright, what infringement looks like and how to avoid it. The book illustrates this with relevant cases and real world examples, including practical, step-by-step guidance for stakeholders of all types. It also signposts the future of copyright in the music industry through an examination of new technologies such as artificial intelligence and blockchain. Key features include: An engaging and approachable writing style A practical orientation for those in the industry and their advisors The impact of social media on copyright infringement, management and remedies Accessible explanations of key concepts in copyright and related rights, as well as commonly misunderstood topics such as sampling and fair use. Musicians, producers, copyright holders and others working in the music industry will find this an indispensable and easy-to-use resource for navigating all aspects of music copyright. It will also be of interest to academics and students of copyright law for its discussion of contemporary issues such as technology and enforcement"--